Improving Interest, Participation and Learning Outcomes in Learning IPS Through The Jigsaw Model Learning Approach - Karnidah, Nely (Economic Education and Entrepreneurship Journal, 2023)
Cooperative learning strives for a student to be able to teach material to other participants. The students are conditioned in a situation where they will interact and discuss and share opinions while indirectly helping to cover up the weaknesses between students. The Jigsaw learning model allows everyone in the class to share ideas and contribute each other's abilities to improve the process of success in learning. This classroom action research took place at SMP Negeri 9 Kotabumi, Talang Bojong village, Lampung. The research was carried out for 3 months, from 1 August to 31 October 2018. The researcher involved two colleagues as observers. The author plans research using the Kemmis and Taggart model designs using the stages: Planning, Action, and Observation, followed by Reflection for each cycle. Based on the results of the study, student achievement or learning outcomes through the Jigsaw cooperative learning model experienced a significant increase. In cycle I with a class average of 62.71 it increased in cycle II to 74.79 and in cycle III to 84.79. Likewise, student learning activities both individually and in groups experienced a significant increase in discussions, teacher-student interaction, student interaction.Keywords: Cooperative Learning, Jigsaw Types, Classroom Action Research, Learning OutcomesDOI: http://dx.doi.org/10.23960/E3J/v6i1.65-70